2018
DOI: 10.1073/pnas.1806476115
|View full text |Cite
|
Sign up to set email alerts
|

Observation of highly stable and symmetric lanthanide octa-boron inverse sandwich complexes

Abstract: While boron forms a wide range of metal borides with important industrial applications, there has been relatively little attention devoted to lanthanide boride clusters. Here we report a joint photoelectron spectroscopy and quantum chemical study on two octa-boron di-lanthanide clusters, LnB (Ln = La, Pr). We found that these clusters form highly stable inverse sandwich structures, [Ln-B-Ln], with strong Ln and B bonding via interactions between the Ln 5d orbitals and the delocalized σ and π orbitals on the B … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
66
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(77 citation statements)
references
References 47 publications
10
66
1
Order By: Relevance
“…PE measurements and infrared photodissociation (IR-PD) spectra in combination with rst-principles theory calculations have proven to be powerful approaches in characterizing novel clusters in gas phases. [3][4][5][6][7][17][18][19][20][21][22][23][24][25][26][27][28]62 As shown in Fig. 4, the highsymmetry Ta 3 B 12 À (3) exhibits relatively simple IR and Raman spectral patterns, with the major IR active peaks at 507 (e 0 ), 559 (e 0 ), 668 ða 00 2 Þ, and 881 (e 0 ) cm À1 (Fig.…”
Section: Simulated Ir Raman and Pe Spectra Of Ta 3 B 12 à (3)mentioning
confidence: 99%
“…PE measurements and infrared photodissociation (IR-PD) spectra in combination with rst-principles theory calculations have proven to be powerful approaches in characterizing novel clusters in gas phases. [3][4][5][6][7][17][18][19][20][21][22][23][24][25][26][27][28]62 As shown in Fig. 4, the highsymmetry Ta 3 B 12 À (3) exhibits relatively simple IR and Raman spectral patterns, with the major IR active peaks at 507 (e 0 ), 559 (e 0 ), 668 ða 00 2 Þ, and 881 (e 0 ) cm À1 (Fig.…”
Section: Simulated Ir Raman and Pe Spectra Of Ta 3 B 12 à (3)mentioning
confidence: 99%
“…[25][26][27][28] Recently, we have found that di-lanthanide The Journal of Chemical Physics ARTICLE scitation.org/journal/jcp octaboron clusters (Ln 2 B 8 − ) can form remarkable inverse sandwiches. 29 There have been few experimental studies of boron clusters doped by group V elements except B n N − (n = 1-3). [30][31][32] Computational studies have been reported on B n N 2 (n = 1-6) and B n P 2 (n = 1-7) clusters, 33,34 as well as a joint experimental and theoretical study on the isoelectronic Bi 2 Al n (n = 1-4) clusters.…”
Section: Introductionmentioning
confidence: 99%
“…To aid in the simulation of PE spectra, a standalone program named AutoPES is also developed. Recent study on PrB 7 − , CoB 18 − , and Ln 2 B 8 − clusters shows that the TGMin‐2 program and the AutoPES program are powerful tools for the global minimum structure search of free and surface‐adsorbed molecules and nanoclusters. With these implementations and improvements, the TGMin‐2 program can become a useful tool for cluster science and heterogeneous catalysis.…”
Section: Discussionmentioning
confidence: 99%
“…TGMin‐2 has been used to determine global minimum structures of several different metal‐doped boron clusters, which have been published or will be published soon . Here, we provide the global minimum search results of PrB 7 − and CoB 18 − as examples of the application of TGMin‐2.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation